5+1 Stories of Habitation: Literary Representations of Habitation in Athens of the Crisis - Moira, Maria (Design/Arts/Culture, 2024)
The article explores the representation of urban space and human habitation in Greek literature, particularly in the aftermath of the financial crisis that began in 2008. The narrative focuses on the city of Athens as it grapples with economic turmoil, the shock of the pandemic, and the ongoing war in Ukraine.